(untitled) (Al-Academy, 2024)
Modern technology is a powerful tool in the teaching process for different stages of education, as it provides a set of benefits that enhance the teaching and learning processes as it provides digital reading platforms and smart applications, and the opportunity to have immediate access to a wide range of stories and anecdotes, which encourages the diversity of children’s reading and broadens their horizons. cultural; There is no doubt that the availability of digital stories for children enables direct interaction with texts and cognitive content, as this type of stories combines audio, animation, and interactions that enhance the pleasure of reading and make children feel greater participation in the world of the story and a deep understanding with a broad imagination that leads to innovation and creativity. The current research project aims to take advantage of the capabilities of artificial intelligence technology in drawing some Omani folk stories through the use of the descriptive analytical approach and the quasi-experimental approach as effective means of transferring stories and anecdotes to the world of children, while providing opportunities for digital reading platforms and smart phone applications for children and access to... Rich and diverse content of Omani intangible heritage stories in modern, contemporary forms with ease. The project to digitize Omani popular stories in digital form is considered one of the basic outputs of this project, with opportunities to apply them in the educational aspect in ways characterized by creativity and innovation through applications of artificial intelligence technology